2016
DOI: 10.1002/cpt.386
|View full text |Cite
|
Sign up to set email alerts
|

Zika virus: A new human teratogen? Implications for women of reproductive age

Abstract: In 2015 an unprecedented increase of reports of newborns with microcephaly in Brazil made news headlines around the world. A possible etiological association with prenatal maternal infection by Zika virus (ZIKV) was suggested based on temporal and geographic distribution of ZIKV infection and the subsequent increase in the reports of microcephaly cases. Here we discuss ZIKV as a new human teratogen, with comments on potential treatment options.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 14 publications
(12 reference statements)
1
22
0
Order By: Relevance
“…The suspicion of a causal relationship between microcephaly and ZIKV, and the preliminary evidence of a specific clinical phenotype beyond isolated microcephaly in a study of 35 infants by Schuller‐Faccini et al, prompted us to study in greater detail the phenotypic spectrum of this newly recognized pattern of disruption, as well as to speculate regarding the underlying developmental pathogenesis (PAHO, ; Schuler‐Faccini, Ribeiro, et al, ; Schuler‐Faccini, Sanseverino, et al, ). Assuming the current evidence as sufficient for causality, the phenotypes described in these 83 infants most likely result from ZIKV prenatal infection of the embryo and fetus (Brasil, Pereira, Moreira, et al, ; de Araújo et al, ; França et al, ; Honein et al, ; Rasmussen, Jamieson, Honein, & Petersen, ; Schuler‐Faccini, Sanseverino et al, ). This study provides detailed insight into the range of the phenotypes observed in these infants.…”
Section: Discussionmentioning
confidence: 99%
“…The suspicion of a causal relationship between microcephaly and ZIKV, and the preliminary evidence of a specific clinical phenotype beyond isolated microcephaly in a study of 35 infants by Schuller‐Faccini et al, prompted us to study in greater detail the phenotypic spectrum of this newly recognized pattern of disruption, as well as to speculate regarding the underlying developmental pathogenesis (PAHO, ; Schuler‐Faccini, Ribeiro, et al, ; Schuler‐Faccini, Sanseverino, et al, ). Assuming the current evidence as sufficient for causality, the phenotypes described in these 83 infants most likely result from ZIKV prenatal infection of the embryo and fetus (Brasil, Pereira, Moreira, et al, ; de Araújo et al, ; França et al, ; Honein et al, ; Rasmussen, Jamieson, Honein, & Petersen, ; Schuler‐Faccini, Sanseverino et al, ). This study provides detailed insight into the range of the phenotypes observed in these infants.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical presentation of ZIKV embryopathy cases, including arthrogryposis, increased skin fold in the occipital region, alterations in neurological and imaging tests compatible with the classic clinical picture of ZIKV infection (brain calcification and delayed brain development) as described in the literature, was crucial for diagnosis 15,16 .…”
Section: Discussionmentioning
confidence: 98%
“…Beside microcephaly, brain calcifications, cataracts and intraocular calcifications of eyes in fetuses are also reported [45]. In other cases, agyria, hydrocephalus and associated cortical displacement and mild focal inflammation are also present [46][47][48]. Similarly in another case in addition to the above-mentioned symptoms,…”
mentioning
confidence: 91%